Mode of Peroxisome Proliferator-Activated Receptor gamma Activation by Luteolin - Puhl, Ana C.; Bernardes, Amanda; Silveira, Rodrigo L.; Yuan, Jing; Campos, Jessica L. O.; Saidemberg, Daniel M. [UNESP]; Palma, Mario Sergio [UNESP]; Cvoro, Aleksandra; Ayers, Stephen D.; Webb, Paul; Reinach, Peter S.; Skaf, Munir S.; et al. (Amer Soc Pharmacology Experimental Therapeutics, 2012)
The peroxisome proliferator-activated receptor gamma (PPAR gamma) is a target for treatment of type II diabetes and other conditions. PPAR gamma full agonists, such as thiazolidinediones (TZDs), are effective insulin sensitizers and anti-inflammatory agents, but their use is limited by adverse side effects. Luteolin is a flavonoid with anti-inflammatory actions that binds PPAR gamma but, unlike TZDs, does not promote adipocyte differentiation. However, previous reports suggested variously that luteolin is a PPAR gamma agonist or an antagonist. We show that luteolin exhibits weak partial agonist/antagonist activity in transfections, inhibits several PPAR gamma target genes in 3T3-L1 cells (LPL, ORL1, and CEBP alpha) and PPAR gamma-dependent adipogenesis, but activates GLUT4 to a similar degree as rosiglitazone, implying gene-specific partial agonism. The crystal structure of the PPAR gamma ligand-binding domain (LBD) reveals that luteolin occupies a buried ligand-binding pocket (LBP) but binds an inactive PPAR gamma LBD conformer and occupies a space near the beta-sheet region far from the activation helix (H12), consistent with partial agonist/antagonist actions. A single myristic acid molecule simultaneously binds the LBP, suggesting that luteolin may cooperate with other ligands to bind PPAR gamma, and molecular dynamics simulations show that luteolin and myristic acid cooperate to stabilize the Omega-loop among H2', H3, and the beta-sheet region. It is noteworthy that luteolin strongly suppresses hypertonicity-induced release of the pro-inflammatory interleukin-8 from human corneal epithelial cells and reverses reductions in transepithelial electrical resistance. This effect is PPAR gamma-dependent. We propose that activities of luteolin are related to its singular binding mode, that anti-inflammatory activity does not require H12 stabilization, and that our structure can be useful in developing safe selective PPAR gamma modulators.